PERANCANGAN CONSERVATORY CENTER UNIVERSITAS TANJUNGPURA - Oktafiansyah, Muhammad Arshy; Zain, Zairin; Kalsum, Emilya (JMARS: Jurnal Mosaik Arsitektur, 2024)
Indonesia is an archipelagic country located in a tropical climate with abundant diversity of flora, fauna, and microorganisms. This diversity makes Indonesia a natural laboratory for plants, with great potential in the field of agriculture. However, with the continuous growth of population, agricultural land is diminishing, presenting a significant challenge in achieving food security for the nation. Therefore, it is important to strive for food sources with methods and efforts that can maintain the sustainability of natural resources in the future. In facing these challenges, Universitas Tanjungpura in West Kalimantan can play a role as one of the supporting institutions in maintaining future sustainability. One of its efforts is through the conservation of species and ecosystems by providing facilities such as the Conservatory Center. The design process of the Conservatory Center involves several stages, including collecting primary and secondary data through literature studies, analysis, synthesis, evaluation, and reevaluation. The Conservatory Center serves three main functions: conservation and education, management and services, and support. Through its design, the Conservatory Center at Universitas Tanjungpura creates an environment similar to the natural habitat of the plants within it. With three radial masses, the building optimizes lighting for its facilities, including conservation areas, laboratories, management areas, services, and a food court.